Preparation and characterization of self-assembled ZnO nanowire devices: nanowire strain sensor and homogeneous p–n junction. (17th September 2021) - Liu, Wei; Wen, Zhicheng; Chen, Sizhen; Wang, Chunqing; An, Rong; Zhang, Wei; Wang, Xinming; Wang, Junjie; Tian, Yanhong
Abstract: In this work, intrinsic and p-type ZnO nanowires (NWs) have been synthesized. Pure intrinsic ZnO nanowires have been fabricated by direct oxidation method and their aspect ratio reached up to 271.3. Sb-doped ZnO nanowires were uniformly grown on Si substrates by chemical vapor deposition with diameters ranging from 0.5 to 5 μ m and lengths ranging from 100 μ m to 3 mm. Directional arrangement of nanowires has been realized by two self-assembly methods, pulling method and water flow method, and two kinds of ZnO nanodevices (strain sensor and homogenous p–n junction) were prepared and characterized based on the directional arranged nanowires. According to the current response of ZnO nanowire strain sensor, the deformation quantities of elastic plate under the action of external forces in orthogonal X and Y direction were calculated respectively. The ZnO nanowire homogenous p–n junction was made of two vertical Sb-doped and intrinsic ZnO nanowires. The I – V characteristic curve showed good rectification characteristics, and the forward turn-on voltage was about 10 V. However, since the current was too small due to the small carrier concentration in the ZnO single crystal, it is difficult to achieve electroluminescence at present.